VARIASI FONOLOGI BAHASA INDONESIA PADA KOMUNITAS PENUTUR BAHASA MAKASSAR (Indonesian Language Phonological Variation of Makassarese Speakers Community) - Ramlah Mappau (SAWERIGADING, 2014)
The Indonesian language usage of community and certain age could be the second language, whilst local language could be the first or mother tongue. Indonesian language could be influenced by the first language. It causes the phonological variation in pronouncing certain words that is not suitable with Indonesian language grammar. Method applied to find out the phonological variation used by Makassar language community in speaking Indonesian is descriptive qualitative method by listening-noting technique. It is used to describe Indonesian language phonological variation on Makassarese speakers community. Data obtained by the speech of researched object, based on result of data analysis is sound alteration, sound omission, and sound addition.